Optimization of Acidic Isoamylase Production by Isolated Bacillus coagulans. Issue 3 (2011) - Allah, Magdy A. Gad; Ghazy, Eman A.; Bayoumi, Reda A.; El-louboudy, Samier S.; Elsoud, Mostafa M. Abo
No abstract available